Application of the NIOSH-Modified Holmberg-Persson Approach to Perimeter Blast Design - Stephen Iverson; Chick Kerkering (International Society of Explosives Engineers, 2008)
Perimeter control blasting is common in civil construction projects but not as common in mining. A poorly designed and executed underground mine development blast design can result in unwanted wall rock damage. This damage increases the risk of rock falls and injury. With the availability of good drilling equipment, it is a simple matter to add the few extra holes needed to change conventional drifting into drifting with perimeter control.